Design, simulation and analysis of micro electro‐mechanical system microneedle for micropump in drug delivery systems - Srinivasa R. Karumuri; Hamza Mohammed; Koushik Guha; Ashok K. Puli; Ameen Einsanwi; Girija S. Kondavitee (IET Nanobiotechnology)
Abstract This article reports on the mechanical strength analysis and flow characteristics of square tip and circular tip microneedles by employing highly potent drugs that are given in extremely little quantity (microlitres) using MEMS technology, which proves to be a significant component of micropump in the application of Bio‐MEMS. These microneedles are well suitable for a MEMS‐based micropump in the drug delivery systems. It is an essential part of the micropump through which the drug is released into the patient’s body. The proposed microneedles can withstand a stress of 23 MPa and 20 KPa. An extensive investigation on selection of material for the microneedle is carried out to meet the requirements of the biocompatibility and high yield, as well as tensile strength. As mighty drugs such as vasopressin, atropine and digoxin are administered in large quantities, the microneedle is designed so as to deliver 800 µl of drug, with each microneedle delivering 90 µl. in a 3 3 array. 3 × 3 array releasing 90 µl.